Science Fiction in Historical and Cultural Literary Discourse - Siderevičiūtė, Simona (Respectus Philologicus, 2014)
This work intends to complement literary studies in science fiction. It discusses the history of global science fiction, overviews the most characteristic features of its historical periods, and provides an introduction to Lithuanian science fiction, indicating its main features and topics. In the context of culture, science fiction is often defined as a literary genre with the emphasis on its nature as fiction. Only rarely are the history of the origin of science fiction, its variations, and the pioneers of science fiction whose works are still highly valued taken into account. Science fiction is often criticized through the filter of preconceived ideas that consider this type of literature to be “frivolous.” This article discusses the possible reasons for such an approach. In Lithuania, this genre is still associated only with pop literature, and its expression cannot yet equal the works of foreign authors. The basic classical motifs of global science fiction found in Lithuanian science fiction include: representatives of extraterrestrial civilizations and human contact with them, scientists and inventors, agents of military institutions, and space travel. Lithuanian science fiction writers follow the traditions of global science fiction when using these classical motifs; however, a general lack of original and individual themes, motifs, and manifestations may be observed.
Keywords: literature; science fiction; criticism; fictitiousness; genre; novum